Innovative hydrogels in cutaneous wound healing: current status and future perspectives - Sawadkar, Prasad; Lali, Ferdinand; Garcia-Gareta, Elena; Garrido, Beatriz Gil; Chaudhry, Abdullah; Matharu, Priya; Kyriakidis, Christos; Greco, Karin (Frontiers in Bioengineering and Biotechnology, 2025)
Chronic wounds pose a substantial burden on healthcare systems, necessitating innovative tissue engineering strategies to enhance clinical outcomes. Hydrogels, both of natural and synthetic origin, have emerged as versatile biomaterials for wound management due to their structural adaptability, biocompatibility, and tunable physicochemical properties. Their hydrophilic nature enables efficient nutrient transport, waste removal, and cellular integration, while their malleability facilitates application to deep and irregular wounds, providing an optimal microenvironment for cell adhesion, proliferation, and differentiation. Extracellular matrix (ECM)- based hydrogels retain bioactive molecules that support cellular infiltration, immune modulation, and tissue remodelling, making them highly effective scaffolds for growth factor delivery and regenerative therapies. Additionally, their injectability and potential for in situ polymerization enable minimally invasive applications, allowing on-demand gelation at target sites. By modifying their mechanical properties through crosslinking, hydrogels can achieve enhanced structural stability, prolonged degradation control, and improved surgical handling, optimizing their functionality in dynamic wound environments. This review outlines current approaches to skin tissue engineering, examining the biomaterials employed in hydrogel design, their limitations, and their interactions with host tissues. Furthermore, it highlights the emerging potential of functionalized injectable hydrogels, particularly those engineered for controlled drug release, enhanced bioactivity, and patient-specific therapeutic applications. These hydrogels offer a transformative platform for advanced wound care and regenerative medicine.